Implementasi Sistem Kontrol Temperatur Pada Proses Pemanggangan Ubi Cilembu Menggunakan Oven Berbasis Mikrokontroler - Toni Agung Wicaksono; Aad Hariyadi; Koesmarijanto Koesmarijanto (Politeknik Negeri Malang, 2020)
Indonesia has a famous sweet potato called Ubi Cilembu that has a chewy and attractive meat structure. The advantages of this sweet potato, if baked in an oven, will produce a sweet honey flavor. Cilembu Sweet Potato that does not taste honey when eaten will reduce the delicacy because during the roasting process using an oven, there is no temperature control system that causes not toasted properly. Since reversing Cilembu yams is still done manually which can be endangering workers if exposed to a hot part of the oven. Because of this, the researcher will make it easier for users to work on the cilembu sweet potato roasting process more effectively than an oven control system is made. The implementation system is done by entering the temperature setpoint value and the timer via the remote displayed on the LCD, then the data is sent using a wireless module when the oven's half-timer time will rotate automatically by using the servo metal gear. The results are carried out by using a remote temperature control in the oven by entering the temperature setpoint value and the timer via the remote displayed on the LCD, then the data is sent using the wireless module when the furnace timer half time in the oven will rotate automatically using a metal servo gear. The system performance is designed to work within 2 hours with a weight of 1 kg of cilembu sweet potato using a temperature of 100.50 ° C.